Linking rules en el impuesto sobre utilidades costarricense (Un análisis de la acción 2 del Plan BEPS de OCDE) - Vargas Gámez, Jorge Daniel (2026)
This paper aims at analyzing hybrid mismatch regulation and its  linking rules within Income Tax Law N° 7092 in relation to BEPS Action 2 of the OECD. It describes the international background of new Section 9 paragraph m) of Income Tax Law N° 7092 and its tax benefits, followed by a brief reflection on its individualized application.